PENANGGULANGAN PENYALAHGUNAAN NARKOBA OLEH ANAK MELALUI BIMBINGAN KONSELING - Evy Septiana Rachman (Jurnal Bimbingan Penyuluhan Islam, 2021)
Initially, narcotics were intended for medical treatment, their use has been misused, ironically the perpetrators of narcotics abuse are children / adolescents, this problem has a tremendous impact on the continuity of this nation's next generation Prevention and handling of narcotics abuse by children / adolescents is carried out differently from the process for adults, where the process for children is guided by the Child Protection Law, the Child Justice Law, and the Child Welfare Law. The judicial process for cases of narcotics abuse by children, actually focuses on rehabilitation, not merely imposing criminal sanctions. Criminalization is considered to have more negative impacts on children or adolescents who are given criminal sanctions, for example the future of children or adolescents will have a bad record, negative stigma against ex-convicts from society and others. Rehabilitation can be carried out in two forms, namely medical rehabilitation and rehabilitation through counseling guidance. Besides being able to improve the child's condition both physically and psychologically, Rehabilitation is also able to find the starting point for the problem of deviant behavior or delinquent behavior (delicacy) of children or adolescents. By finding the root of the problem, the problem of illegal trafficking and the abuse of narcotics can be overcome.